Multi-beam interferometric patterning in optically transparent materials - Tham, Nicholas (2019)
A method to directly pattern nanoscale periodic features within optically transparent solid materials by means of a configurable multi-beam femtosecond laser interference is proposed. While femtosecond micromachining of optically transparent solid materials has been explored in great detail in the recent past, research in direct interference patterning on such materials has not been well established. Therefore, different design considerations such as complete void formation and flexibility of the patterned substrate are investigated as part of this study. The relationship between intensity distributions and actual void formation in optically transparent materials is also investigated to establish critical parameters for pattern formation. It is envisaged that this proposed method and data obtained may enable to explore the untapped domains of developing substrates for solid-state 3D microbattery applications.